Inclusive Islamic Education In The Darul Amin Border of Tenggara Aceh - Asari, Hasan; Mukti, Abd; Kahar, Syadidul (International Journal for Educational and Vocational Studies, 2020)
The problem that is analyzed in this article is about the concept and implementation of inclusive Islamic education in the Darul Amin Border Dayah in Southeast Aceh. This research is a qualitative study with a phenomenological approach by examining how the functions of the implementation of inclusive Islamic education in the Dayah Border Darul Amin Aceh Tenggara. Inclusive Islamic education in Dayah Border Darul Amin is integrated into the implementation of the dayah curriculum, both the dayah curriculum, the formal curriculum, the informal curriculum and the non-formal curriculum. Inclusive values instilled in dayah daily life are the values of tolerance, togetherness, mutual assistance, respect for differences and leadership based on Islamic values. The essence of inclusive Islamic education in the Darul Amin Border Dayah is the leader of the ummah and the generation of Muslim believers who are highly virtuous, knowledgeable, free-thinking and devoted to society.